Research progress in the preparation of high value added chemicals by directional pyrolysis of biomass - WU Gang; XIAO Rui; ZHANG Huiyan* (能源环境保护)
The production of petroleum-based chemical products, which are used in various daily and industrial goods such as cosmetics, lubricants, plastic products, and synthetic fibers, has led to a heavy dependence on petroleum as a raw material. As a result, there has been widespread attention on the production of high-value platform chemicals using renewable biomass as feedstock. Biomass pyrolysis offers a selective approach to produce a variety of high-value platform chemicals, and it has become a frontier and hotspot in global research. This article provides a systematic overview of the production of commonly used high-value chemicals through biomass pyrolysis. Firstly, it summarizes the effects of pyrolysis feedstock, pyrolysis techniques, pretreatment methods, reaction temperature, reaction time, and catalysts on the production of target high-value products. Secondly, it analyzes the reaction pathways for the production of target products through biomass pyrolysis. Finally, the future development directions for the production of platform chemicals through biomass direct thermochemical conversion are explored, providing a basis and reference for the efficient conversion and utilization of biomass.